2013
DOI: 10.4103/0019-5545.105515
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of restless leg syndrome in subjects with depressive disorder

Abstract: Background:Restless legs syndrome (RLS) is known to be associated with depression. We hypothesized that RLS in depression is linked to the severity, duration, and frequency of depressive episodes.Materials and Methods:Subjects fulfilling DSM-IV-TR criteria of depressive disorders were included in this study after seeking informed consent. Using structured interview of MINI-Plus their demographic data and history were recorded. Severity of depression was assessed with the help of HAM-D. Insomnia was diagnosed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The prevalence of restless legs symptoms was 24.8% in the controls. Respectively, previous population studies have reported the prevalence of restless legs syndrome that estimates as high as 24% [43][44][45], and among patients with depression the prevalence that estimates as high as 31.5% [46]. The association between TNF-α and depression is not significant constantly; for instance, obesity may confuse the correspondence [47].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of restless legs symptoms was 24.8% in the controls. Respectively, previous population studies have reported the prevalence of restless legs syndrome that estimates as high as 24% [43][44][45], and among patients with depression the prevalence that estimates as high as 31.5% [46]. The association between TNF-α and depression is not significant constantly; for instance, obesity may confuse the correspondence [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that our patient suffered from depression and RLS. Gupta et al’s cross-sectional assessment found a 31.5% prevalence of RLS among patients diagnosed with MDD [ 34 ]. A high rate of depression has also been reported in patients with RLS, although prevalence rates seem to be related to RLS severity [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathogenesis of RLS is unknown ( 1 ). RLS patients especially have difficulty falling asleep or maintaining sleep ( 1 2 ). Criteria for the diagnosis of RLS were first introduced by the International Restless Leg Syndrome Study Group (IRLSSG) in 2003 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…RLS patients especially have difficulty falling asleep or maintaining sleep ( 1 2 ). Criteria for the diagnosis of RLS were first introduced by the International Restless Leg Syndrome Study Group (IRLSSG) in 2003 ( 2 ). According to these, the urge to move the legs, worsening of symptoms with rest or inactivity, improvement with movement and impairment during evening or night hours compared to daytime are the diagnostic indicators of RLS ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation